Professional Cultural Migration in the Digital Age: An Intercultural Communication Study of Digital Immigrant Lecturers in the Dynamics of Academic Workload Reporting (BKD) at Tanjungpura University, Pontianak - Wuysang, Julia Magdalena; Patriani, Ira; Musa, Dahniar Th.; Rahmawati, Rahmawati; Pijoh, Feibe Engeline (Technium Social Sciences Journal, 2025)
In the digital era, the Academic Workload Reporting System (BKD) has evolved beyond its administrative function to become a site of cultural negotiation, particularly for lecturers from the digital immigrant generation. This study explores how senior academics—whose professional identities were shaped in the pre-digital era—undergo identity transformation when confronted with a reporting system rooted in efficiency, quantification, and technocratic logic. Employing a qualitative methodology and a critical digital ethnographic approach, the research investigates intercultural communication dynamics between senior lecturers and younger administrative staff, with digital systems conceptualized as symbolic actors within the higher education institution. Findings reveal three key insights:1.The adaptation process of digital immigrant lecturers unfolds in three phases—identity dissonance, resistance or accommodation, and identity reconstruction;2. Intergenerational differences in communication styles, shifting power relations within the organization, and evolving meanings of academic professionalism significantly affect the effectiveness of interactions within digital BKD reporting;3.Lecturers respond through symbolic strategies, collaborative practices, and a redefinition of their roles as digital academics. A critical discovery highlights that three lecturers have persistently refused to participate in the digital BKD system as a form of boycott, while one has even opted for early retirement from the civil service. These cases underscore that digital transformation in academia is not merely a technological shift, but a cultural migration that demands a fundamental reconstruction of values and working relationships within the academic ecosystem.